(untitled) (TAMADDUN NURI JURNALI, 2025)
The article discusses the theoretical and practical aspects of the formation and development of critical thinking in students of the philological direction in the process of studying the humanities. Special attention is paid to the definition of the essence of critical thinking as an integral ability, including analytical, reflective, logical and interpretative thinking. It is shown that the humanities (philosophy, literature, linguistics, cultural studies, etc.) have a high potential for stimulation of mental activity and the development of an independent position of students.